Human leucocyte antigen alleles confer susceptibility and progression to Graves’ ophthalmopathy in a Southern Chinese population - Huang, Xiaosheng; Liu, Guiqin; Mei, Shaoyi; Cai, Jiamin; Rao, Jing; Tang, Minzhong; Zhu, Tianhui; Chen, Wenchiew; Peng, Shiming; Wang, Yan; Ye, Ye; Zhang, Tong; et al. (British journal of ophthalmology, 2021)
PurposeTo evaluate the contributions of human leucocyte antigen (HLA) class I and II genes in the development of Graves’ ophthalmopathy (GO) in a Southern Chinese population.MethodsEight HLA loci were genotyped and analysed in 272 unrelated patients with Graves’ disease (GD) or the proptosis and myogenic phenotypes of GO, and 411 ethnically matched control subjects.ResultsThe allele frequencies of HLA-DRB1*16:02 and -DQB1*05:02 in the GD, proptosis and myogenic groups, HLA-B*38:02 and -DQA1*01:02 in the myogenic group were significantly higher than those in the control group, respectively (all corrected p values <0.05, OR >2.5). The haplotype frequencies of HLA-DRB1*16:02-DQA1*01:02-DQB1*05:02 and HLA-DRB1*16:02-DQA1*01:02-DQB1*05:02-DPA1*02:02-DPB1*05:01 in the proptosis and myogenic groups, and HLA-A*02:03-B*38:02-C*07:02 and HLA-A*02:03-B*38:02-C*07:02-DRB1*16:02-DQA1*01:02-DQB1*05:02-DPA1*02:02-DPB1*05:01 in the myogenic group were significantly higher than those in the control group respectively (all corrected p values <0.05, OR >2.5). The potential epitopes (‘FLGIFNTGL’ of TSHR, ‘IRHSHALVS’, ‘ILYIRTNAS’ and ‘FVFARTMPA’ of IGF-1R) were fitted exactly in the peptide-binding groove between HLA-DRA1-DRB1*16:02 heterodimer, and the epitopes (‘ILEITDNPY’ of THSR, ‘NYALVIFEM’ and ‘NYSFYVLDN’ of IGF-1R) were also fitted exactly in the peptide-binding groove between HLA-DQA1*01:02-DQB1*05:02 heterodimer.ConclusionsThe HLA-DRB1*16:02 and -DQB1*01:02 alleles might be risk factors for GD including the proptosis and myogenic phenotypes of GO. The alleles HLA-B*38:02, -DQA1*01:02, the HLA haplotypes consisting of HLA-B*38:02, -DRB1*16:02, -DQA1*01:02 and -DQB1*05:02 might be susceptibility risk factors for GO. Simultaneously, some epitopes of TSHR and IGF-1R tightly binding to groove of HLA-DRA1-DRB1*16:02 or HLA-DQA1*01:02-DQB1*05:02 heterodimers might provide some hints on presenting the pathological antigen in GO.